2017
DOI: 10.1002/ejlt.201700032
|View full text |Cite
|
Sign up to set email alerts
|

Pomegranate seed oil organogels structured by propolis wax, beeswax, and their mixture

Abstract: The capability of propolis wax, beeswax, and their mixture to gel pomegranate seed oil (PSO) was studied. Samples were prepared increasing the concentration of waxes in pomegranate seed oil from 5 to 15% w/w. After propolis wax, beeswax, and PSO chemical characterization, thermal, and structural properties of wax-based organogels were studied. Both propolis wax and beeswax formed organogel thanks to the presence of crystal networks made of needle-like β′-form crystals. Based on FTIR spectroscopy, mainly van de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
17
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 32 publications
8
17
0
2
Order By: Relevance
“…Similar observations were also reported by Morales-Rueda et al (2009) studying CLW crystal network in sunflower oil and Sánchez-Becerril et al (2018) studying CLW crystal network in high-oleic safflower oil. In agreement with other literatures, Fayaz, Goli, Kadivar, Valoppi, Barba, Balducci, et al (2017) reported needle-like crystals of BW and PW oleogels in which the BW organogel contained smaller crystals than PW sample.…”
Section: Characterizationsupporting
confidence: 93%
See 2 more Smart Citations
“…Similar observations were also reported by Morales-Rueda et al (2009) studying CLW crystal network in sunflower oil and Sánchez-Becerril et al (2018) studying CLW crystal network in high-oleic safflower oil. In agreement with other literatures, Fayaz, Goli, Kadivar, Valoppi, Barba, Balducci, et al (2017) reported needle-like crystals of BW and PW oleogels in which the BW organogel contained smaller crystals than PW sample.…”
Section: Characterizationsupporting
confidence: 93%
“…In the Yılmaz and Öğütcü (2014a) study, olive oil organogels of BW and SW exhibited very similar XRD pattern and the main peaks were at 4.1 and 3.7 A˚, related to the orthorhombic perpendicular subcell. Similar pattern implicating this polymorph has been observed for CRW, CLW, and RBW gels with olive oil (Dassanayake et al, 2009), SW, CRW, and BW gels with hazelnut oil (Öğütcü & Yılmaz, 2015;Yılmaz & Öğütcü, 2014b), PW, and BW gels with PSO (Fayaz, Goli, Kadivar, Valoppi, Barba, Balducci, et al, 2017), and canola, sesame, sunflower, and flaxseed oil oleogels of PW . This polymorph with desirable attributes (homogeneous, smooth and creamy) can be used as a partial replacement for hard fat in products such as shortening, margarines, and spreads that need β′ polymorph of triglycerides .…”
Section: Characterizationsupporting
confidence: 78%
See 1 more Smart Citation
“…The loss of the flaxseed oil during the rheological measurement could be the reason of a more compact network oleogel with higher G’ value. Oleogels presented similar values to others prepared with 5–15% beeswax, propolis wax, a mixture of both (Fayaz et al , ), with a combination of 5% ethylcellulose (EC) and 5% surfactant (Gallego et al , ).…”
Section: Resultssupporting
confidence: 75%
“…Based on our previous researches, propolis wax was identified as an efficient structuring agent for organogel formation and displayed the potency to apply as a partial replacement of fat phase in chocolate spread (Fayaz et al, 2017a,b). To modify the organogel behavior, mixture of beeswax and propolis wax was suggested (Fayaz et al, 2017c). In this study, we aimed to improve crystal structure and thermal properties of propolis wax-based organogel using powerful method of HIU.…”
Section: Introductionmentioning
confidence: 99%